Diversification strategies to improve cocoa farmers’ household income: the case of Côte d’Ivoire - Bonna Antoinette Tokou; Bonna Antoinette Tokou; Claudia Coral; Claudia Coral; Flora Isabella Montiel; Flora Isabella Montiel; Constant Yves Adou Yao; Constant Yves Adou Yao; Stefan Sieber; Stefan Sieber; Katharina Löhr; Katharina Löhr (Frontiers in Sustainable Food Systems)
Diversification is a strategy adopted by farming households to meet several challenges. However, there is a lack of empirical evidence to support these positions. We contribute to filling this research gap by providing quantitative evidence of the impact of diversification on the additional income of cocoa-producing households. This study aims to analyze income from the diversification strategies of cocoa producers by building the typology of the most common systems and assessing their impacts on household income. A survey of 303 households across five Côte d’Ivoire regions reveals that cocoa producers have four distinct types of production systems, namely: (1) simple cocoa production systems; (2) cocoa production systems with crops in association; (3) cocoa production systems combined with income generating diversification on the additional plot; and (4) cocoa production systems, and food cropland. Of the four systems, type 3 is the most widely adopted by cocoa producers, generating higher income per household than the other types due to the large part of perennial income that requires a larger area. Furthermore, type 2 presents the best cocoa yield. We also assessed differences per population group. Thus, the results show that women adopt type 2 and type 4 systems with less surface area and are more devoted to the production of subsistence crops. Non-Ivorian producers have systems with higher cocoa yields and income from diversification than Ivorian producers. However, only 7% of producers have access to financing enabling them to invest in diversification crops. The findings demonstrate that crop diversification strategies can successfully improve households’ living income and ensure the sustainability of cocoa production.